What should fiscal councils do? - Lars Calmfors, L; Wren-Lewis, S (Blackwell Publishing, 2011)
Fiscal watchdogs, so-called fiscal councils, have been proposed as a method to counter deficit bias of fiscal policy. The paper analyses theoretically what role fiscal councils could play and surveys empirically the activities of existing councils. Case studies of the Swedish Fiscal Policy Council and the UK Office for Budget Responsibility are done. It is concluded that fiscal councils should be advisory, rather than decision-making, and work as complements, rather than substitutes, to fiscal rules. Although no panacea, fiscal councils could play a useful role by at the same time strengthening fiscal discipline and allowing rules-based fiscal policy to be more flexible. A key issue is their political fragility and how their long-run viability should be secured. Three ways of guaranteeing their independence are suggested: (1) reputation-building; (2) formal national rules; and (3) international monitoring.